Removal from liver transplantation list of a hepatitis C virus‐HIV co‐infected patient after successful treatment with sofosbuvir and daclatasvir. Issue 3 (9th June 2016) - Llaneras, J.; Castells, L.; Santos, B.; Crespo, M.; Puig, T.; Esteban, J.I.; Esteban, R.
Abstract: We present a human immunodeficiency virus‐infected patient with severe decompensated hepatitis C virus‐related cirrhosis awaiting liver transplantation (LT) who received a 24‐week course of interferon/ribavirin‐free antiviral treatment with sofosbuvir and daclatasvir on a compassionate basis. Rapid viral suppression was associated with progressive improvement of his liver function tests. The patient achieved a sustained virological response and concomitant clinical improvement, which prompted removal from the LT list 12 weeks after the end of treatment.